2015
DOI: 10.3109/00016489.2015.1015608
|View full text |Cite
|
Sign up to set email alerts
|

Acute hearing loss in patients with hematological disorders

Abstract: Acute sensorineural hearing loss in a patient with leukemia or aplastic anemia may be related to either sudden sensorineural hearing loss or endolymphatic hydrops. A significant sequential decline in the function of the cochlea, saccule, utricle, and semicircular canals indicates that the pars inferior is more vulnerable to blood insult than the pars superior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have suggested an association between anemia and hearing loss [25][26][27]. In one study, the authors described 12 cases of SSNHL in 14 patients with leukemia or aplastic anemia [25]. A prospective cross-sectional study reported that 11.2% (10/89) of patients with sickle cell anemia had hearing loss [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested an association between anemia and hearing loss [25][26][27]. In one study, the authors described 12 cases of SSNHL in 14 patients with leukemia or aplastic anemia [25]. A prospective cross-sectional study reported that 11.2% (10/89) of patients with sickle cell anemia had hearing loss [26].…”
Section: Discussionmentioning
confidence: 99%
“…Another theory is that biochemical and electrical imbalances in the inner ear of anemic patients could result in endolymphatic hydrops and SSNHL. A few previous studies have reported endolymphatic hydrops in patients with hematologic disorders such as anemia or leukemia [25,33].…”
Section: Discussionmentioning
confidence: 99%
“…Hematological disorders such as aplastic anemia, sickle cell anemia, and hyperviscosity syndrome have been described as being associated with inner ear deficits. These hematological diseases may cause inner ear hemorrhage or vasculopathy ( 53 ).…”
Section: Etiological Comorbiditiesmentioning
confidence: 99%
“…Lin et al ( 53 ) reported that during the 20 years, they had identified 14 cases of SSNHL among patients with hematological disorders, i.e., leukemia or aplastic anemia. Most of these patients presented an abnormal mean hearing level, cervical vestibular-evoked myogenic potential test, ocular vestibular-evoked myogenic potential test, and caloric test results, exhibiting a significant sequential decline in inner ear function.…”
Section: Etiological Comorbiditiesmentioning
confidence: 99%
“…Since then, it has become apparent that otologic manifestations of hematologic malignancies are common, with a reported incidence of 32% to 69% in patients with leukemia (3)(4)(5). While the incidence of otologic symptoms in patients with lymphoma has not been addressed in the literature, symptoms have included those of serous otitis media, conductive hearing loss, otalgia, and aural fullness (6)(7)(8). The incidence of otologic symptoms secondary to multiple myeloma is also unknown but isolated reports have found asso-ciations with hearing loss and vertigo (9,10).…”
Section: Introductionmentioning
confidence: 99%